Efficacy of intrathecally administered fentanyl versus dexmedetomidine for cesarean section: a double blinded, randomized clinical trial - Athanasia Tsaroucha; Aliki Tympa Grigoriadou; Tania Moshovou; Kassiani Theodoraki; Aikaterini Melemeni (Clinical and Experimental Obstetrics & Gynecology)
Background: Dexmedetomidine, a highly selective α2 agonist has been studied in the past for its use as adjuvant to local anesthetics for spinal anesthesia. Fentanyl has also been used as a spinally administered adjuvant to various local anesthetics. The aim of this study was to investigate the duration of motor and sensory block along with the hemodynamic parameters, neonatal Apgar scores, postoperative analgesia and maternal satisfaction of overall anesthetic/analgesic regimen in parturients under ropivacaine 0.75% plus dexmedetomidine or fentanyl spinal anesthesia. Methods: Forty patients American Society Of Anesthesiology (ASA) I or II, scheduled for elective cesarean section were studied. Patients were randomly allocated to receive ropivacaine 0.75% 1.6–2 mL plus 10 μg fentanyl (Group F, n = 20) or ropivacaine 0.75% 1.6–2 mL plus 10 μg dexmedetomidine (Group D, n = 20), intrathecally. The primary outcome was duration of motor and sensory block. Secondary outcomes were:neonatal Apgar scores in the first and fifth minute, additional postoperative analgesia, time to first postoperative analgesic dose and maternal satisfaction of overall anesthesia and analgesia. Results: Patients in dexmedetomidine group (Group D) had prolonged duration of motor and sensory block when compared to patients in fentanyl group (Group F). Mean duration of motor block was significantly higher in Group D than in Group F (163.75 min versus 124.75 min respectively, p = 0.013). Regression of the sensory block to T8 was significantly prolonged for Group D (158.50 min Group D versus 114.25 min in Group F, p = 0.021). Neonatal Apgar scores, additional postoperative analgesia, time to first postoperative analgesic dose and maternal satisfaction of overall anesthesia/analgesia process, did not statistically differ between the groups. Conclusions: Intrathecal dexmedetomidine is associated with prolonged motor and sensory block. Its profile is similar to fentanyl in terms of cardiovascular stability, sedation, Apgar scores, patient satisfaction and postoperative analgesia.